The process and role of the judiciary in election administration dispute resolution in Indonesia - Eny Kusadarini; Anang Priyanto; Sri Hartini (Jurnal Civics: Media Kajian Kewarganegaraan, 2021)
Election administrative violations occur at the time of the implementation of the general election by election organizers and contestants. Sometimes, they do not realize that they have committed a violation. Since the general election during the reformation period after the fall of the New Order in Indonesia, there have been frequent violations of election administration resolved through administrative courts through the State Administrative Court. The dispute resolution was carried out after complaints were made through Bawaslu and DKPP as administrative dispute resolution (ADR) institutions and did not bring results.  This administrative violation is considered detrimental to the candidate contesting the election, causing a dispute between the candidate contesting the election and the organizers of the general election. This article examines the process of resolving electoral administrative disputes in Indonesia and the judiciary's role in resolving electoral administrative disputes. Several examples of cases of election administration violations that occurred and their causes obtained through empirical studies using the technique of documenting judges' decisions that have permanent legal force at the Supreme Court of the Republic of Indonesia were analyzed using inductive logic.